Ibn Sina’s Conception of the Ideal Teacher: A Classical Islamic Framework for Modern Pedagogy - Asma Akram Butt,; Dr.Rukhsana Sardar,; Mishal Siyab, (Dialogue Social Science Review (DSSR), 2025)
This qualitative research study explores Ibn Sina’s Conception of the Ideal Teacher within a classical Islamic philosophical framework and examines its relevance to contemporary educational models. The central aim was to identify the key qualities, responsibilities, and pedagogical approaches associated with Ibn Sina’s vision of the ideal teacher, and to assess how these ideas align with or diverge from modern theories of teaching and learning. The study utilized document analysis as the primary method of data collection, focusing on primary texts such as Kitab al-Shifa (The Book of Healing) and Kitab al-Najat (The Book of Salvation), alongside secondary sources including academic commentaries, peer-reviewed journal articles, and scholarly books. A total of 15 textual sources comprising 5 primary texts and 10 secondary scholarly works were purposefully selected for their direct relevance to Ibn Sina’s educational philosophy. To further contextualize these findings within modern pedagogical discourse, 12 journal articles and 3 academic books published between 2000 and 2024 were analyzed, offering a comparative lens to interpret Ibn Sina’s enduring influence. Additionally, semi-structured interviews were conducted with five Islamic education scholars from Pakistan and Malaysia, selected through purposive sampling based on their expertise and scholarly contributions in Islamic philosophy and pedagogy. These interviews added interpretive depth and validated the emerging themes from the textual analysis. The findings highlight that Ibn Sina’s model of the ideal teacher marked by intellectual mastery, moral integrity, emotional sensitivity, and spiritual responsibility remains highly relevant and applicable to modern education, particularly in ethics-based and values-driven teacher education programs. Keywords: Ibn Sina, ideal teacher, Islamic philosophy of education, pedagogy, document analysis, teacher training, constructivism, moral education